Palm olein organogelation using mixtures of soy lecithin and glyceryl monostearate - Ghan, Sheah Yee; Siow, Lee Fong; Tan, Chin Ping; Cheong, Kok Whye; Thoo, Yin Yin (MDPI AG, 2022)
The present work investigated the interaction between soy lecithin (SL), glyceryl monostearate (GMS), and water in structuring palm olein (PO) to create an organogel having similar mechanical properties to commercial spread. Extreme vertices mixture design was used to optimize the composition of PO-based organogel. The resulting model showed a good fit to the predicted data with R2 ≥ 0.89. The optimum composition was 8% SL, 22% GMS, 28% water, and 42% PO (w/w) to produce a mean firmness of 1.91 N, spreadability of 15.28 N s−1, and oil binding capacity (OBC) of 83.83%. The OBC of optimized organogel was 10% higher than commercial spread product, and no significant difference was observed in the mechanical properties (p > 0.05). The microstructure, as well as the rheological and thermal properties of the optimized organogel were characterized. Fourier transform infrared analysis indicated that hydrogen bonding and van der Waals interactions were the key driving forces for organogelation. The mixture of SL and GMS favored the formation of β′ + β form crystals with a predominance of the β′ form. These results have important implications for the development of PO-based organogel as a potential fat replacer in the production of low-fat spread.